Barriers and Facilitators to Community Health Worker Outreach and Engagement in Detroit, Michigan: A Qualitative Study. Issue 6 (November 2022) - Lapidos, Adrienne; Kieffer, Edith C.; Guzmán, Rebeca; Hess, Kristen; Flanders, Tessana; Heisler, Michele
An effective approach to engaging populations who face health care access barriers is support from community health workers (CHWs). There is little research, however, on specific barriers and facilitators related to two key areas of CHW practice: outreach, defined as the ability to make any initial contact with the priority population, and engagement, defined as the ability to continue to work with the priority population after initial contact is made. The current qualitative study is ancillary to a randomized evaluation of a CHW-led program for Medicaid Health Plan enrollees. Implementation experiences with outreach and engagement led the evaluators to develop the current study in which health plan and nonhealth plan CHWs (n = 12) serving low-income, predominantly Black populations in Detroit participated in qualitative semistructured interviews to elucidate barriers and facilitators to outreach and engagement. All audio recordings were transcribed verbatim. The study team used inductive qualitative data analysis techniques. Barriers to outreach included inaccurate contact information and mistrust. Barriers to engagement included lack of ability to provide needed resources, leading to hopelessness and diminished trust, and discontinuity of services due to eligibility changes and terminated programs. Facilitators included adapting outreach schedules and strategies to community needs, availability of resources, and relational strategies that leveraged CHW social proximity. Further research should systematically investigate the relative success of different CHW-led outreach and engagement strategies for specific populations so as to better design and implement CHW programs.